2022
DOI: 10.1101/2022.05.20.492863
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Adaptor Protein 2 (AP2) complex modulates habituation and behavioral selection across multiple pathways and time windows

Abstract: Animals constantly perceive and integrate information across sensory modalities, and their nervous systems must select behavioral responses appropriate to the current situation and prior experience. Genetic factors supporting this behavioral flexibility are often disrupted in neuropsychiatric conditions, and our previous work revealed the disease-associated ap2s1 critically supports habituation learning in acoustically-evoked escape behavior of zebrafish. ap2s1 encodes a subunit of the AP2 endocytosis adaptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 110 publications
(199 reference statements)
1
1
0
Order By: Relevance
“…Moreover, our data are consistent with a model in which our pharmacogenetic perturbations lead to broad impacts on brain activity. Finally, these data are consistent with the reported hypersensitivity of all of the tested mutants to low-intensity stimuli [ 25 , 28 , 29 , 33 ], which suggest baseline deficits in the thresholding of acoustic stimuli. Importantly, although habituation deficits may co-occur with changes in response thresholds as they do in these mutants, these deficits may also occur independently [ 25 , 42 ], suggesting that they are mechanistically separable.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, our data are consistent with a model in which our pharmacogenetic perturbations lead to broad impacts on brain activity. Finally, these data are consistent with the reported hypersensitivity of all of the tested mutants to low-intensity stimuli [ 25 , 28 , 29 , 33 ], which suggest baseline deficits in the thresholding of acoustic stimuli. Importantly, although habituation deficits may co-occur with changes in response thresholds as they do in these mutants, these deficits may also occur independently [ 25 , 42 ], suggesting that they are mechanistically separable.…”
Section: Discussionsupporting
confidence: 89%
“…We recently identified a splice site mutation in the adaptor related protein complex 2 subunit sigma 1 ( ap2s1 ) gene, positioning the AP-2 adaptor complex as a fifth genetic regulator of habituation learning. We previously demonstrated that besides its role in habituation learning, AP-2 modulates sensorimotor decision-making via the Calcium-Sensing Receptor, CaSR [ 27 , 33 ]. Yet whether AP-2 also modulates NMDA, dopamine, or glycinergic signaling to regulate habituation learning has not been examined.…”
Section: Resultsmentioning
confidence: 99%